Quinone‐Based Redox Supercapacitor Using Highly Conductive Hard Carbon Derived from Oak Wood. (7th October 2019) - Katsuyama, Yuto; Nakayasu, Yuta; Oizumi, Kotaro; Fujihara, Yui; Kobayashi, Hiroaki; Honma, Itaru
Abstract: In this study, the use of biorefined wood materials in the fabrication of organic redox supercapacitors is proposed. Oak‐derived hard carbon (HC) is revealed to have a nanographite domain structure, showing conductivity as high as that of artificial graphite. The CO2 ‐activated hard carbon (A–HC) has a conductivity one order higher than that of commercial activated carbon, with a surface area of 1126 m 2 g −1 . The energy densities of supercapacitors composed of a tetrachlorohydroquinone cathode and anthraquinone (AQ) or 1, 5‐dichloroanthraquinone (DCAQ) anode are 19.0 and 13.8 Wh kg −1, respectively. The utilization rate of AQ with A–HC is 97.6% (250.9 mAh g −1 ), which is much higher than those in previous reports (≈80%). After 1000 cycles, 91.0% of the discharge capacity is retained when the DCAQ anode is used. Biorefined wood materials lead to a remarkable improvement in the operation of organic supercapacitors. This is intriguing, because the functional carbon material herein is easily prepared from a natural resource, wood, whereas numerous studies have prepared such materials from artificial chemical sources. Therefore, the use of oak‐derived HC enhances the usability of organic active materials for energy storage devices and potentially has a far‐reaching impact on the environment. Abstract : Hard carbon (HC) is easily prepared by Japanese traditional carbonization of oak wood, showing a conductivity as high as that of artificial graphite. The use of oak‐derived hard carbon for quinone‐based organic supercapacitors dramatically improves the utilization rate of anode active material (97.6%) while that in conventional reports using petroleum‐derived activated carbon is 80% at most.